Hydrology and stream water quality of fire-prone watersheds - Pacheco, Fernando (2021)
This study reviewed current research on the nexus ‘wildfireswatershed hydrology-stream water quality’. Various studies used remote sensed Earth observation data to improve the understanding of soil erosion and water balance in burned watersheds and their relationships with fire variables (e.g., severity). It was noteworthy the application of computer models to assess fire-related hydrologic processes (e.g., soil-water repellence) and their control over runoff generation. The discussions about short-term and long-term impacts of wildfires were prominent, including streamflow reductions following vegetation resprouts or mobilization of metals. The controls of wildfire impacts drove studies about the role of spatial scale in the rainfall thresholds for postfire runoff and sediment delivery or the role of snowpack decline in the anticipation of peak flows in Boreal latitudes. Finally, it is worth mentioning the research on fire management, as a measure to restore stream water yields in forested watersheds and prevent subsequent fires